Structural relationships among software engineering capabilities in Japan. (1st January 2012) - Kadono, Yasuo; Tsubaki, Hiroe; Tsuruho, Seishiro
This study aims at better understanding how software engineering capabilities should be improved in the drastically changing IT industry in Japan. Based on the results of path analyses on the three surveys data from 151 IT firms, human development and R&D are significantly fundamental capabilities to improve the quality of deliverables. Also, improving capabilities of project management and process improvement are significantly an immediate effect on deliverables. On the contrary, quality assurance and customer contacts might need long-term efforts to be successful. The results suggest that order effects among the software engineering capabilities are verified based on the data-centric approach.